1998
DOI: 10.1016/s0893-133x(97)00111-5
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine Versus Placebo and Haloperidol: Quality of Life and Efficacy Results of the North American Double-Blind Trial

Abstract: This double-blind study evaluated the impact of treatment with olanzapine compared with haloperidol, and placebo on improvements in symptomatology and quality of life in patients with a DSM-III-R diagnosis of schizophrenia. A total of 335 patients was randomized to five treatment groups; olanzapine 5 +/- 2.5 mg/day, olanzapine 10 +/- 2.5 mg/day, olanzapine 15 +/- 2.5 mg/day, haloperidol 15 +/- 5 mg/day, and placebo. Patients responding to treatment during the 6-week acute phase were eligible to enter a 46-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
5

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(43 citation statements)
references
References 28 publications
3
35
0
5
Order By: Relevance
“…Olanzapine displayed efficacy in treating negative symptoms in a 24-week extension study, but there was no statistically significant difference between olanzapine and haloperidol in reducing negative symptoms (Hamilton et al 1998). A path-analysis of acute-phase studies found that most of the changes in negative symptoms could not be explained by other compounds (positive symptoms, depression, EPS) .…”
Section: Negative Symptomsmentioning
confidence: 92%
“…Olanzapine displayed efficacy in treating negative symptoms in a 24-week extension study, but there was no statistically significant difference between olanzapine and haloperidol in reducing negative symptoms (Hamilton et al 1998). A path-analysis of acute-phase studies found that most of the changes in negative symptoms could not be explained by other compounds (positive symptoms, depression, EPS) .…”
Section: Negative Symptomsmentioning
confidence: 92%
“…The recently developed clozapine-like atypical neuroleptic, olanzapine, is also effective in treating the negative symptoms of schizophrenia (Beasley et al 1996;Hamilton et al 1998) and shares similar neuropharmacological profiles with clozapine, including receptor binding (Bymaster et al 1996a), noradrenaline release in the mPFC (Li et al 1998;Westerink et al 1998) and preferential Fos induction in the mPFC (Robertson and Fibiger 1996;Sebens et al 1998). Previous studies have shown that Fos expression induced by noradrenaline in the frontal cortex is mediated mainly by ␤ -adrenoceptors (Bing et al 1992;Stone and Zhang 1995).…”
Section: The Atypical Neuroleptics Clozapine and Olanzapine Have Sumentioning
confidence: 99%
“…Although clozapine is known to have an affinity for various neurotransmitter receptors, such as noradrenergic, dopaminergic, histaminergic, muscarinic and 5-hydroxytryptamine (5-HT) receptors, the precise neuropharmacological action of clozapine that results in the induction of Fos expression in the mPFC is unknown. Since clozapine administration increases the firing rate of noradrenergic cells in the locus coeruleus (LC) and noradrenaline release from nerve terminals in the mPFC (Ramirez and Wang 1986;Li et al 1998;Westerink et al 1998), it is possible that clozapine-induced noradrenaline release activates cortical neurons in the mPFC.The recently developed clozapine-like atypical neuroleptic, olanzapine, is also effective in treating the negative symptoms of schizophrenia (Beasley et al 1996;Hamilton et al 1998) and shares similar neuropharmacological profiles with clozapine, including receptor binding (Bymaster et al 1996a), noradrenaline release in the mPFC (Li et al 1998;Westerink et al 1998) and preferential Fos induction in the mPFC (Robertson and Fibiger 1996;Sebens et al 1998). Previous studies have shown that Fos expression induced by noradrenaline in the frontal cortex is mediated mainly by ␤ -adrenoceptors (Bing et al 1992;Stone and Zhang 1995).…”
mentioning
confidence: 99%
“…The utility of the QLS in assessing change in deficit status has been highlighted in treatment studies (eg Meltzer et al, 1990;Rosenheck et al, 1997;Hamilton et al, 1998). The importance of the QLS in assessing outcome in schizophrenia research has also been highlighted by the observed relation between neurocognitive impairment and psychosocial status (Green, 1996;Buchanan et al, 1994;Medalia et al, 1998;Wykes et al, 1999).…”
Section: Introductionmentioning
confidence: 99%